Presidential Control of Independent Agencies' Leadership and Personnel: A Two‐Case Study of Interbranch Contestation over the Bureaucracy and the Unitary Executive under Donald Trump. Issue 1 (18th January 2022) - Dodds, Graham G.
Abstract: This article assesses recent developments in the interbranch struggle over control of the bureaucracy, specifically independent federal agencies and the impact of the unitary executive theory during the presidency of Donald Trump. It examines controversies that involved two Supreme Court cases about independent agencies: Lucia v. SEC (2018), which addressed administrative law judges and the president's appointment power, and Seila Law v. CFPB (2020), which addressed agency leadership and the president's removal power. The two cases have received some attention from legal scholars, but they are not well known among presidency scholars, and they are important for understanding how the unitary executive theory and the interbranch struggle over control of the bureaucracy have developed in recent years .